Effect of borage and zinc in the fruit traits of three eggplant varieties Egg plant Solanum melongenal L - Al - Obeidi, Abdul Rasul Hamid Hussein; Alwan, Othman Khaled (Journal of agricultural, environmental and veterinary sciences, 2019)
A field experiment was carried out at the research department of the Department of Horticulture and Garden Engineering of the Faculty of Agriculture- Diyala University during the agricultural season 2017 to study the effect of varieties and nutrients on the growth characteristics of three eggplant varieties. On 27- 2- 2017 seeds were planted The experiment included two factors: the first factor is the varieties of the class Black Beauty and Vzlh V1 and the local variety (Abu torso) and called V2 Syrian class Vzlh V3, The second factor is the boron (F1) and p2100 (F2) feeder concentrations, with a concentration of 100 ppm for each element and the treatment of F4, which was sprayed with distilled water. The experiment included twelve global treatments, Randomized Complete Block Design (RCBD) and showed the following results:1.The fruit (V2) was superior to the rest of the varieties in the number of fruits per plant, fruit length, plant yield and total yield, with 24.82 fruits, 1, 15.70 cm and 4.03 kg. (1) and 85.344 tons (1) respectively, while V3 was significantly higher than the rest of the varieties in the rate of fruit weight and diameter, with a rate of 163.14 g and fruit of 1 and 6.44 cm respectively.2.The superiority of the spraying treatment of F3 for boron and zinc with their synthesis with concentration of 100 ppm for boron and 100 ppm for zinc in the ratio of the number of fruits, the weight, the length and the diameter of the fruit With 27.72 fruits, 1 plant, 169.63 g, fruit 1, 16.02 cm, 6.0 cm, 4.77 kg, 1 plant and 100.192 tons. Ha 1 respectively.3.The treatment of V2F3 interference was superior to the rest of the parameters in the ratio of the number of fruits, fruit weight, length, and the rate of the total plant yield and the total number, which reached 31.76 fruits, plants and 193.10 g, fruit 1, 17.70 cm, 6.14 kgand115. 33 tons. hectare respectively. For the fruit diameter rate, the interference treatment of V3F3 exceeded 7.38 cm.
Keywords: eggplant varieties; foliar application; micronutrients